2011
DOI: 10.1002/app.34424
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic behavior of polymer tape in a wound roll

Abstract: in Wiley Online Library (wileyonlinelibrary.com).ABSTRACT: A viscoelastic computational model is developed that uses experimentally determined viscoelastic material properties as input and can be used to predict the behavior of a tape material in a wound roll as stresses relax over time. Experimental creep test results are used to find best-fit creep-compliance parameters to describe two high density data storage tape media. The two tapes used in the analysis are a developmental tape with a poly(ethylenenaphth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…investigates the viscoelastic behavior of an orthotropic tape material using numerical methods, and is an extension of a previously developed isotropic viscoelastic model [2]. Previous studies have shown that creep compliance data obtained using LTO3 and developmental tape products [7] can be used as input to an isotropic viscoelastic model which can predict the evolution of the wound-in tape stresses over time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…investigates the viscoelastic behavior of an orthotropic tape material using numerical methods, and is an extension of a previously developed isotropic viscoelastic model [2]. Previous studies have shown that creep compliance data obtained using LTO3 and developmental tape products [7] can be used as input to an isotropic viscoelastic model which can predict the evolution of the wound-in tape stresses over time.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (a) shows a schematic of the geometry of the wound roll. In (b), the radial and tangential stresses are shown on a single layer of tape [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These parameters can be estimated by several techniques that utilize the response of the material to a properly selected external excitation. It is commonplace that estimates for the parameters are 1 found by a least squares fit to measurement data, see, for example, (Vuoristo et al, 2000;Sorvari and Malinen, 2007;Weick, 2009;Acton and Weick, 2011). A particular feature of mechanical analog models for viscoelastic materials, consisting of arrangements of springs and dashpots, is that the number of material parameters, that is, the number of springs and dashpots, is not fixed beforehands.…”
Section: Introductionmentioning
confidence: 99%